Erythropoietin receptor regulates tumor mitochondrial biogenesis through iNOS and pAKT - Aboouf, Mostafa A.; Guscetti, Franco; von Büren, Nadine; Armbruster, Julia; Ademi, Hyrije; Ruetten, Maja; Meléndez-Rodríguez, Florinda; Rülicke, Thomas; Seymer, Alexander; Jacobs, Robert A.; Schneider Gasser, Edith M.; Aragones, Julian; et al. (Frontiers in Oncology, 2022)
Erythropoietin receptor (EPOR) is widely expressed in healthy and malignant tissues. In certain malignancies, EPOR stimulates tumor growth. In healthy tissues, EPOR controls processes other than erythropoiesis, including mitochondrial metabolism. We hypothesized that EPOR also controls the mitochondrial metabolism in cancer cells. To test this hypothesis, we generated EPOR-knockdown cancer cells to grow tumor xenografts in mice and analyzed tumor cellular respiration via high-resolution respirometry. Furthermore, we analyzed cellular respiratory control, mitochondrial content, and regulators of mitochondrial biogenesis in vivo and in vitro in different cancer cell lines. Our results show that EPOR controls tumor growth and mitochondrial biogenesis in tumors by controlling the levels of both, pAKT and inducible NO synthase (iNOS). Furthermore, we observed that the expression of EPOR is associated with the expression of the mitochondrial marker VDAC1 in tissue arrays of lung cancer patients, suggesting that EPOR indeed helps to regulate mitochondrial biogenesis in tumors of cancer patients. Thus, our data imply that EPOR not only stimulates tumor growth but also regulates tumor metabolism and is a target for direct intervention against progression.